Dampak Ekonomi Terhadap Pergaulan Bebas dari Perspektif Hukum - S. Hadi, Muh. Hartarto; Rhamadan, Putra; Supriyadi, Supriyadi; Desiana, Rifka; Prasetya, Muhammad Rafly; Kairuddin, Kairuddin; Pransisto, Johamran (Lembaga Penelitian dan Pengbdian Masyarakat (LP2M) Institut Ilmu Sosial dan Bisnis Andi Sapada, 2025)
The phenomenon of free association, particularly involving sexual behavior outside of marriage, has significant economic implications. This paper examines the economic impact of free association from a legal perspective, exploring how it affects individuals, families, and society. The primary economic concerns include increased healthcare costs due to sexually transmitted infections (STIs) and unintended teenage pregnancies, which impose a financial burden on both public health systems and affected individuals. Additionally, the disruption of education due to early pregnancies and health issues can lead to reduced productivity and lower human capital quality, negatively impacting long-term economic growth. The legal perspective is crucial in managing and mitigating these economic impacts. Effective laws and regulations can set clear boundaries and provide protections, especially for vulnerable groups such as teenagers. Legislation on the legal age for sexual activity and comprehensive sex education can help reduce risky behaviors associated with free association. Moreover, laws supporting access to reproductive health services and counseling are vital in minimizing negative economic consequences. This paper aims to analyze how legal frameworks can be optimized to address the economic challenges posed by free association. The methodology includes a review of existing laws and their effectiveness in managing free association's economic impacts, as well as case studies demonstrating successful legal interventions. The goal is to provide recommendations for policy improvements that align with both economic stability and social welfare. By integrating economic and legal perspectives, this paper seeks to highlight the importance of a synergistic approach to managing free association. Effective legal measures not only uphold social and moral norms but also contribute to economic well-being, ensuring a balanced and healthy society.